Artificial Intelligence in Information Technology: Enhancing Efficiency, Security, and Innovation A Descriptive Review - Dr. Abid Ghaffar; Dr. Arfan Arshad; Sara Abbas; Muhammad Tahir (Spectrum of Engineering Sciences, 2024)
This descriptive review explores the role of artificial intelligence (AI) in enhancing efficiency, security, and innovation within the field of information technology (IT). AI-driven technologies are reshaping IT operations, offering automation, predictive analytics, and intelligent decision-making tools that optimize resource management and operational efficiency (Accenture, 2023). In cybersecurity, AI enhances threat detection and response capabilities through anomaly detection and behavioral analysis, enabling real-time protection against increasingly sophisticated cyber threats (Technology Review, 2023). Additionally, AI’s integration into cloud computing and network management supports dynamic resource allocation and real-time traffic monitoring, improving scalability, reliability, and security across IT infrastructures (Gartner, 2023). However, the study acknowledges limitations, including reliance on secondary data and a narrow focus on specific applications. Future research should address these gaps by investigating real-world applications and exploring the ethical and environmental implications of AI in IT. This paper’s findings highlight AI's transformative potential across various IT domains while underscoring the need for responsible and sustainable AI practices. These insights contribute to a deeper understanding of how AI can drive progress and innovation in IT, while informing both academic discussions and industry practices. Keywords: Artificial Intelligence (AI), Information Technology (IT), AI-driven Efficiency